Optimization of ultrasound-assisted extraction of pectinase enzyme from guava (Psidium guajava) peel: enzyme recovery, specific activity, temperature, and storage stability - Amid, Mehrnoush; Murshid, Fara Syazana; Manap, Mohd Yazid; Sarker, Md. Zaidul Islam (Taylor and Francis Ltd., 2016)
This study aimed to investigate the effects of the ultrasound-assisted extraction conditions on the yield, specific activity, temperature, and storage stability of the pectinase enzyme from guava peel. The ultrasound variables studied were sonication time (10-30min), ultrasound temperature (30-50 degrees C), pH (2.0-8.0), and solvent-to-sample ratio (2:1mL/g to 6:1mL/g). The main goal was to optimize the ultrasound-assisted extraction conditions to maximize the recovery of pectinase from guava peel with the most desirable enzyme-specific activity and stability. Under the optimum conditions, a high yield (96.2%), good specific activity (18.2U/mg), temperature stability (88.3%), and storage stability (90.3%) of the extracted enzyme were achieved. The optimal conditions were 20min sonication time, 40 degrees C temperature, at pH 5.0, using a 4:1mL/g solvent-to-sample ratio. The study demonstrated that optimization of ultrasound-assisted process conditions for the enzyme extraction could improve the enzymatic characteristics and yield of the enzyme.